TRENDS IN STATUS OF HYPERTENSION IN SOUTH CHINA: RESULTS FROM TWO REPRESENTATIVE CROSS-SECTIONAL SURVEYS, 2012-2017. (April 2021) - Liu, Lin; Huang, Yuqing; Huang, Jiayi; Yu, Yuling; Chen, Chaolei; Shen, Geng; Feng, Yingqing
Abstract: Objective: This study aims to investigate the long-term natural trends in the status of hypertension in south China from 2012–2017. Design and method: Two successive cross-sectional surveys were conducted in Guangdong Province in 2012 and 2017, which include 10970 and 36376 participants aged 35 to 75 from different area, respectively. A multistage, stratified and cluster random sampling method was used to enroll the participants. Hypertension was defined as a mean systolic blood pressure at least 140mmHg and/or a mean diastolic blood pressure at least 90 mmHg, and/or self-reported use of antihypertensive medication within past 2 weeks, according to the 2010 Chinese guidelines for the management of Hypertension. The prevalence and control rates of hypertension were also estimated according to the 2017 American College of Cardiology/American Heart Association (ACC/AHA) high blood pressure guideline. Results: In 2012, 39.3% participants had hypertension, whereas 37.6% participants had hypertension in 2017. The age-standardized prevalence was 34.7% [95% confidence interval (CI): 34.1–35.2] and 31.9% (95% CI: 31.6–32.2) in 2012 and 2017, respectively. The prevalence of prehypertension decreased from 14.5 to 13.1% from 2012 to 2017. Over the two study periods, 45.6 and 51.2% of those with hypertension were aware of their diagnosis in 2012 and 2017, respectively, and 40.8 and 44.9% were taking antihypertensive medications, respectively; the control rates increase from 15.1 to 17.0% and among those who received medical treatment 36.9 and 37.9% achieved control of BP, respectively. Based on the 2017 ACC/AHA guideline, prevalence of hypertension was 64.5% in 2012 and 59.1% in 2017. The control rate increased from 3.0 to 4.4% during this period. And among participants who received medical treatment, only 12.2 and 15.2% of participants achieve the target of hypertensive management in 2012 and 2017, respectively. Conclusions: During 2012 to 2017, the prevalence of hypertension in South China trended to be stable, and the rate of awareness, treatment and control increased but still low. Figure. No caption available.